RENAISANCE KESUSASTRAAN JAWADI KARATON SURAKARTA - Restu Budi Setiawan, Kundharu Saddhono, Restu Budi Setiawan, Kundharu Saddhono (Jurnal IKADBUDI, 2018)
RENAISANCE KESUSASTRAAN JAWADI KARATON SURAKARTA Restu Budi Setiawan, Kundharu SaddhonoUniversitas Sebelas Maret kundharu.uns@gmail.com Abstract This is a research journal consisting javanesse literature which developed in Jawa Baru particularly in Karaton Surakarta Hadiningrat age. Javanesse literature was advanced at that time. There was diversity of works, such as sastra piwulang, adaptation stories from Javanesse or others old stories even chronicle literature. As described above, it can be called as the renaisance age of Karaton Surakarta Hadiningrat. In this journal, the writter presents various literature works which was created at that particular age. The presentation of this journal literature works that created at Surakarta age are being classified by the influnetial authors. Therefore, the indentities of literature works which created at this Karaton Surakarta Hadiningrat age can be clearly understand. Keywords: literature works, serat, authors, Karaton Surakarta Hadiningrat